A major variation in the virulence of the Asian soybean rust pathogen (Phakopsora pachyrhizi) in Bangladesh. (3rd May 2022) - Hossain, Md. Motaher; Yasmin, Laboni; Rubayet, Md. Tanbir; Akamatsu, Hajime; Yamanaka, Naoki
Abstract: Asian soybean rust (ASR) caused by Phakopsora pachyrhizi is a major threat to soybean production in Bangladesh. Understanding the yearly changes and the current status of pathogenic structures is essential for developing appropriate breeding strategies for obtaining ASR‐resistant soybean lines. Thirty‐four P . pachyrhizi samples were collected from ASR hotspot areas (Chandpur, Lakshmipur, Noakhali, Barisal and Bhola districts) of Bangladesh in 2018 and 2019 and evaluated for pathogenicity on 12 soybean differential lines. The tested samples showed similar and dissimilar pathogenicity patterns on the differentials, yielding 21 distinct pathotypes. The cluster analysis, principal coordinate analysis and principal component analysis of the disease phenotypes of 47 samples collected in 2016, 2018 and 2019 indicated a higher pathogenic diversity and virulence variation in the P . pachyrhizi samples of 2018 and 2019 compared to that of 2016. The pathogenicity profiles of the Bangladeshi P . pachyrhizi samples appeared distinct from those of Argentinian and Brazilian samples, but showed slight similarities with Japanese, Mexican and Paraguayan samples. Furthermore, none of the resistance genes for P . pachyrhizi ( Rpp genes) was solely effective against all the tested samples from 2018 and 2019, while samples (BdRP‐48, BdRP‐56 and BdRP‐58) virulent to all Rpp1–Rpp6 genes were detected. The Rpp ‐pyramided line No6–12–1, carrying Rpp2, Rpp4 and Rpp5, was capable of conferring robust resistance to these virulent samples. Altogether, these results indicate an increase in the virulence of the current ASR pathogen in Bangladesh, which can be resolved by pyramiding different resistance genes in soybean cultivars. Abstract : The virulence of the 2018 and 2019 Asian soybean rust pathogen in Bangladesh has changed significantly from 2016: some samples from 2018 and 2019 were pathogenic to all soybean varieties carrying single resistance genes tested.